PERANCANGAN PUSAT INDUSTRI KREATIF DI TANGERANG SELATAN DENGAN PENDEKATAN ARSITEKTUR HIJAU - Galih Ristendi; Sri Kurniasih; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
The design of a creative industry center with a green architecture approach is a building for activities, such as advertising; architecture; art and antiques market; craft; design; fashion; video, film and photography; interactive games; music; performing Arts; publication and printing; computer and software services; television and radio; and research and development. The development of this creative industry center is a commercial building by applying green architectural approaches such as energy conservation, working with climate, respecting sites, respecting users, limiting new resources, and being holistic. The application of green architecture principal to buildings is such as energy saving resulting from Photovoltaice technology which converts solar thermal energy into electrical energy, buildings are built elongated and thin to maximize lighting, the orientation of the building to sunlight and with the facade material is wood plus a roof garden that functions so that creates a spacious impression, lowers temperature, reduces air pollution and reduces the greenhouse effect. The design of this creative industry center in South Tangerang is due to the low post-pandemic economic growth as well as the still high activity and poverty rate which has resulted in low industrial competitiveness in Indonesia. That way this arrangement is a real step that comes from the utilization of individual creativity, skills and talents to create prosperity and employment.